EKONOMI PADI DI ASIA: SUATU TINJAUAN BERBASIS KAJIAN KOMPARATIF (Forum Penelitian Agro Ekonomi, 2020)
Especially for Asian regions, rice is a strategic commodity because it is a staple food for most of the Asian people. In terms of agricultural land resources availability, several countries have become importers whereas the others exporters. The result of economic study in Asia shows that Cambodia and Thailand have a better agricultural land resource availability to provide rice for their people than the other countries in Asia. The rice farming system is able to give a better life to rice farmers in Malaysia, but it is unable yet to Indonesian rice farmers because of their very small landholding size, even though they have applied intensive technology.  Indonesian food autonomy (for rice) is better than that of several countries in Asia, such as Nepal, Japan, the Philippine and Malaysia.